Pengaruh Keselamatan dan Kesehatan Kerja (K3) Dan Pelatihan Terhadap Kinerja Karyawan pada PT. Kemuning Nusa Indah - Indah Handayani Safitri; Suroso; Flora Patricia Anggela (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the partial and simultaneous effects of occupational safety and health (K3) and training on employee performance at PT. Kemuning Nusa Indah. This study uses a quantitative method with a sample of 93 employees of PT. Kemuning Nusa Indah. Data were collected through questionnaires and analyzed using multiple linear regression with t-test and F-test at a significance level of 5%. The results showed that K3 has a significant effect on employee performance with a t-value of 3.371> 1.987 t table and a significance value of 0.001 <0.05, and training has a significant effect on employee performance with a t-value of 6.276> 1.987 t table and a significance value of 0.000 <0.05. Simultaneously, K3 and training also have a significant effect on employee performance with a calculated F of 189.783> 3.10 F table. Occupational safety and health (K3) and training influence employee performance by 80.8%, while the remaining 19.2% is influenced by other factors that researchers did not examine.